Evolution of benchmarking as a business growth strategy in the 21 st century - Moreira Sornoza , Wilson Gabriel (2026)
The evolution of benchmarking has contributed to the development of companies in various economic sectors where they carry out their business activities. The purpose of applying this tool is to improve processes by comparing one's own practices with those of the competition. However, within organizations, there is a lack of awareness of this technique, which limits the adoption of strategies that could contribute to business growth. In light of this, the present article aims to analyze the evolution of benchmarking as a tool for business growth in the current context, addressing topics that contribute to the stated objective. To this end, a methodology based on documentary-descriptive research was applied, utilizing reliable and impactful bibliographic sources for this study. Companies from different sectors, such as transportation, telecommunications, and services, among others, have opted for benchmarking processes, achieving optimization of their resources as well as their business competitiveness.